2017
DOI: 10.1292/jvms.17-0126
|View full text |Cite
|
Sign up to set email alerts
|

Septicemic invasive <i>Klebsiella pneumoniae</i> infection in a cynomolgus monkey (<i>Macaca fascicularis</i>) with severe diffused suppurative meningoencephalitis

Abstract: A 2-year-old male cynomolgus monkey (Macaca fascicularis) showed neurological symptoms during quarantine for importation into Japan, and was euthanized due to poor prognosis. Gross anatomical examination revealed a hemorrhagic lesion around the lateral ventricle in the cerebrum. Histologically, severe diffused suppurative meningitis and ventriculitis were detected with numerous Gram-negative bacilli in the cerebrum. Immunohistochemically, the bacilli were positively stained with an antibody against Klebsiella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Hypervirulent strains causing IKPS are known to have specific genes, rmpA (a regulator of the mucoid phenotype) and magA (mucoviscosity-associated gene A) which are exclusive for capsule serotype K1 and K2 4,6) . These genes are responsible for hypermucoviscosity of the capsule, making it resistant to phagocytosis 3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypervirulent strains causing IKPS are known to have specific genes, rmpA (a regulator of the mucoid phenotype) and magA (mucoviscosity-associated gene A) which are exclusive for capsule serotype K1 and K2 4,6) . These genes are responsible for hypermucoviscosity of the capsule, making it resistant to phagocytosis 3) .…”
Section: Discussionmentioning
confidence: 99%
“…These genes are responsible for hypermucoviscosity of the capsule, making it resistant to phagocytosis 3) . Determination of hypermucoviscosity is based on a positive string test in which a bacterial colony on an agar plate can be stretched into viscous string of over 5mm in length with an inoculation needle 4) .…”
Section: Discussionmentioning
confidence: 99%
“…It is usually present in the upper respiratory tract of cattle and is isolated from the nasal cavity [ 5 ] or tracheobronchial lavage samples [ 11 ]. Moreover, K. pneumoniae may cause systemic infections, such as septicemia in humans [ 18 , 23 ] and pigs [ 3 ] and meningoencephalitis in humans [ 29 , 30 ] and cynomolgus monkey [ 14 ]. Although Histophilus somni [ 21 ] and Listeria monocytogenes [ 22 ] conventionally cause infectious meningoencephalitis in cattle, neonatal bacterial suppurative meningitis (NBSM) is sporadically caused by Streptococcus bovis [ 28 ], Mannheimia spp.…”
mentioning
confidence: 99%
“…1 calf suffered from sepsis. K. pneumoniae conventionally causes mastitis in cattle [ 6 , 24 ], however, it sometimes causes septic infection in neonatal and elderly humans [ 23 , 29 , 30 ], pigs [ 3 ], and cynomolgus monkeys [ 14 ]. Although it has been reported that K. oxytoca causes meningitis in a calf [ 26 ], to the best of our knowledge, septic infections of K. pneumoniae , including meningoencephalitis, have not been reported in cattle, meaning that our study is the first to report an association between K. pneumoniae and meningoencephalitis.…”
mentioning
confidence: 99%
“…Klebsiella (K.) pneumoniae is a gram-negative, aerobic, nonmotile bacillus of the family Enterobacteriaceae [4]. The bacterium exists widely in surface water, sewage, soil, plants, and the mucosal surfaces of mammals.…”
mentioning
confidence: 99%